RADIATION DAMAGE TO DNA PLASMIDS IN THE PRESENCE OF BOROCAPTATES - Jamborová, Zuzana; Pachnerová Brabcová, Kateřina; Jelínek Michaelidesová, Anna; Zahradníček, Oldřich; Danilová, Irina; Ukraintsev, Egor; Kundrát, Pavel; Štěpán, Václav; Davídková, Marie (Radiation protection dosimetry, 2022)
Boron derivatives have great potential in cancer diagnostics and treatment. Borocaptates are used in boron neutron capture therapy and potentially in proton boron fusion therapy. This work examines modulation effects of two borocaptate compounds on radiation-induced DNA damage. Aqueous solutions of pBR322 plasmid containing increasing concentrations of borocaptates were irradiated with 60Co gamma rays or 30 MeV protons. Induction of single and double DNA strand breaks was investigated using agarose gel electrophoresis. In this model system, representing DNA without the intervention of cellular repair mechanisms, the boron derivatives acted as antioxidants. Clinically relevant boron concentrations of 40 ppm reduced the DNA single strand breakage seven-fold. Possible mechanisms of the observed effect are discussed.
Keywords: plazmidy; DNA; bor; terapie metodou neutronového záchytu (bor-10); poškození DNA; Plasmids; DNA Damage; Boron Neutron Capture Therapy; Boron